SIMASKOT Sebagai Media Layanan Digital Mengukur Tingkat Kepuasan Masyarakat Di DPMPTSP Provinsi Nusa Tenggara Barat - salsabila, elvira; Jailani, Muhammad; Oktaoufy, Famira; Sagita, Suci (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The importance of developing e-government, it can provide benefits for public services, E-Government development must be carried out in Indonesia and the government must carry out digital acceleration to optimize public services, one of which is the West Nusa Tenggara Province Investment and One-Stop Integrated Services Service (DPMPTSP). IT-based public services through the Simaskot Integrated online community satisfaction survey, which is a web-based application that can be accessed by the public, aims to use technology in services to be able to provide convenience to the public and improve service quality. Data collection techniques begin by carrying out outreach activities and using manual questionnaires which are distributed to service users and online questionnaires which are scanned by barcodes directly by service users. The results of this service indicate that it has been rated very well by service users.